2012
DOI: 10.1093/cid/cis1193
|View full text |Cite
|
Sign up to set email alerts
|

Improved Retention Associated With Community-Based Accompaniment for Antiretroviral Therapy Delivery in Rural Rwanda

Abstract: These findings indicate that community-based accompaniment is effective in improving retention, when added to a clinic-based program with fewer patient support mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 37 publications
1
92
1
3
Order By: Relevance
“…Though research on the role of conditional economic incentives in promoting ART adherence has been limited [68], additional studies are ongoing [69]. Food rations and livelihood support may be combined with other support services shown to improve adherence, such as treatment supporters, directly observed therapy, mobilephone text messages, and diary cards [70], and such comprehensive treatment-support programs have been shown to increase ART adherence and retention [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though research on the role of conditional economic incentives in promoting ART adherence has been limited [68], additional studies are ongoing [69]. Food rations and livelihood support may be combined with other support services shown to improve adherence, such as treatment supporters, directly observed therapy, mobilephone text messages, and diary cards [70], and such comprehensive treatment-support programs have been shown to increase ART adherence and retention [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies, reviews or editorials, research published in abstract form only or that did not undergo peer review, studies examining adherence to preor post-exposure prophylaxis or prophylaxis for the prevention of mother-to-child transmission, and any studies that did not report a measure of association between food insecurity or food assistance and adherence were excluded. Methods for the review and inclusion criteria were specified in advance, with the following additional inclusion criteria specified after the full text review: (1) definition of treatment interruption as non-adherence for at least 3 months and exclusion of papers examining treatment interruption as the outcome, (2) exclusion of two papers identified in the search that compared adherence in two groups of wasted HIV patients receiving different types of food supplements [28,29]; and (3) exclusion of studies identified in the search that evaluated combination support programs for PLHIV that included a nutritional component but did not present or permit estimation of the individual effect of food assistance distinct from the other services in the program [30][31][32][33]. Although we did not limit inclusion to adult populations, no studies examined the association between food insecurity and ART adherence in pediatric populations, and only one study examined the association between food assistance and adherence in a pediatric population [34], but was excluded because it did not specify the type of food assistance or the criteria for receiving such support.…”
Section: Study Inclusion Criteriamentioning
confidence: 99%
“…8 Multiple factors must be considered, including mental health, social capital, and variables related to poverty. 11,12 HIV-positive individuals have high rates of depression, [13][14][15] and depressive symptoms have been shown to predict HIV disease progression and mortality in the United States. 16,17 There is evidence that depression is a risk factor for non-adherence to ART in developing contexts, 10,15,18 and management of depressive symptoms is a priority for adherence.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true as large untreated groups of patients in specific districts become less common so that follow-up patients are more geographically dispersed. 23,[27][28][29][30] This study demonstrates potential improvements in costs and outcomes by changing the model of care. Despite significant challenges to patient follow-up, much progress can be achieved through systemized appointments, improved discharge teaching, repeated telephone reminders, assistance with transportation, and outreach follow-up programs.…”
Section: Discussionmentioning
confidence: 76%